Video Made the Calculus Star. Issue 1 (2nd January 2019) - Morena, Matthew A.; Smith, Shelly; Talbert, Robert
Abstract: We describe the use of student-generated video content to assess students' engagement with, and understanding of, problem-solving skills. In this framework, students are tasked with using technology to create videos that show them working through, and explaining solutions to, challenging calculus exercises. The videos are then posted online, accessible only to the students and instructors in the class. Such video assignments align with what recent studies have identified as effective homework practices. Indeed, results from student surveys suggest that a significantly higher level of self-regulated learning takes place in creating these videos than in completing traditional written or online homework.